Simultaneous Endoscopic Endonasal Decompression of the Optic Canal, Superior Orbital Fissure, and Proper Orbital Apex for Traumatic Orbital Apex Syndrome: Surgical Anatomy and Technical Note - Liu, Jianfeng; Zhao, Jianhui; Wang, Yibei; Wang, Zhijun; Li, Rui; Chen, Zhongyan; Zhao, Yu; Han, Jun; Yang, Dazhang (Frontiers in Surgery, 2022)
Objectives: Traumatic orbital apex syndrome (TOAS) is an uncommon but severe ocular complication of craniomaxillofacial fracture. The optimal surgical strategy for TOAS has not been determined. To investigate the endoscopic anatomy of the orbital apex region, propose a protocol for simultaneous endoscopic endonasal decompression of the superior orbital fissure, optic canal and proper orbital apex (EEDCFA) for TOAS and report its use in two patients. Methods: An endoscopic endonasal approach was utilized to dissect the orbital apex region in two silicon-injected adult cadaveric heads. The details of the procedure used for decompression of the orbital apex were determined. The effects of this procedure were determined in two patients with TOAS who underwent simultaneous decompression of the optic canal, superior orbital fissure and proper orbital apex. Results: The orbital apex consisted of three portions, the contents of the optic canal superomedially; the contents of the superior orbital fissure inferolaterally; and the converging portion, or proper orbital apex, anteriorly. From an endoscopic endonasal approach, the optic nerve, superior orbital fissure and orbital apex convergence prominences were found to form a π-shaped configuration. This π-shaped configuration was indicative of the orbital apex and was an important landmark for decompression of the orbital apex. Endonasal decompression of the orbital apex in the two patients resulted in satisfactory recovery of extraocular mobility, with no surgical complications. Conclusions: EEDCFA is feasible, effective and safe for patients with TOAS caused by direct compression of displaced fracture segments. The π-shaped configuration is a valuable landmark for EEDCFA.